How to Run Your Own Online Business: A Gamification Experience in ESL - Mª Ángeles Hernández-Prados; Mª Luisa Belmonte; Juan Carlos Manzanares-Ruiz (MDPI AG, 2021)
Notwithstanding the importance and relevance of gamification as a topical methodology in education, and after a literature review, there are just a few studies using role-playing games. In order to motivate and facilitate English as second language (ESL) learning of first year of Bachillerato (year 12) students at a public high school in the Region of Murcia (Spain) and following an action research methodology, we design, implement and evaluate a role-playing game, which consists of the creation and management of a company, The Tik Tok School. The results confirm that students felt more comfortable speaking in English because they were more motivated. They also state that during the experience they were more focused on learning rather than winning the game and that they prefer a gamification approach over traditional settings. Furthermore, they have been participating constantly using more English than Spanish. After the data analysis, we conclude that this methodology positively impacts motivation and the acquisition of a second language.